Escores clínicos e biomarcadores da resposta inflamatória aguda em pacientes com sepse - Araújo, José Fernandes de (2011)
Sepsis is the expression of a complex network of mediators of inflammation. To define which of these biological indicators discriminate the diagnosis and prognosis is the focus of current researches. To evaluate the role and the diagnostic and prognostic value of lactate, ultrasensitive C-reactive protein (CRP-US), procalcitonin (PCT) and interleukin-6 (IL-6) in adult patients at the ICU with sepsis. Observational, cohort study was conducted between October 2009 and April 2010, enrolling adult patients admitted to two general ICUs of Aracaju, Sergipe, Brazil, diagnosed with severe sepsis (S) or septic shock (SS). There was no interference of researchers in therapeutic regimens and the patients were followed until discharge, death or the 28th day of ICU stay. APACHE II score was calculated at admission (D1) and SOFA score, at D1 and D3. Lactate was measured at D1 and D2 and CRP-US, PCT and IL-6 at D1. The scores and biomarkers were compared between S and SS subgroups and among non-survivors (NS) and survivors (SU). Were evaluated 30 patients, of which S was diagnosed in 23.3% and SS in 76.7% . The mean age was 67.8 ± 18.9 years and it was a single factor predictive of death. Death was the outcome in 53.3% of patients (S = 14.3% and SS = 65.2%). The mean APACHE II was 22.1 ± 8.2 and had good accuracy to predict both the diagnosis and mortality; the mean SOFA at D1 was 9.2 ± 3.5; at D3 was 7.7 ± 3.5, with good accuracy to predict both the diagnosis and mortality; and the Δ SOFA was 1.5 ± 1.5, with no statistical significance. The average of lactate at D1 was 3.7 ± 1.6 mmol/l; at D2 was 2.7 ± 0.7 mmol/l (S = 2.2 ± 0.5; SS = 2.8 ± 0.7); and the lactate clearance was 19.0 ± 39.5. The average of CRP-US was 7.8 ± 14.4 mg / dl (S = 8.9 ± 4.9; SS = 16.0 ± 7.8). The average of PCT was 4.2 ± 8.5 ng / ml and the mean IL-6 was 2.9 ± 0.4 pg / ml. This study showed that the APACHE II and SOFA scores have good accuracy to predict both the diagnosis and mortality among patients with sepsis and that agewas the single factor predictive of death but did not discriminate the diagnosis; the lactate of the second day, and the US-CRP at the admission discriminated the diagnosis, but were unable to predict the outcome; and that the Δ SOFA, lactate clearance, PCT and IL-6 had no discriminatory power in predicting, separately, both the diagnosis and prognosis. Thus, no single biomarker to provide an absolute ability to distinguish sepsis from other inflammatory conditions, nor to monitor and predict its progression or response to treatment; all of them can be used in its proper clinical context, as adjuncts to decision making regarding diagnosis and treatment.